2005
DOI: 10.1111/j.1471-4159.2005.03268.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel D2‐like dopamine receptor with a truncated splice variant and a D1‐like dopamine receptor unique to invertebrates from Caenorhabditis elegans

Abstract: We have cloned two novel Caenorhabditis elegans dopamine receptors, DOP-3 and DOP-4. DOP-3 shows high sequence homology with other D2-like dopamine receptors. As a result of alternative splicing, a truncated splice variant of DOP-3, DOP-3nf, was produced. Because of the in-frame insertion of a stop codon in the third intracellular loop, DOP-3nf lacks the sixth and seventh transmembrane domains that are found in the full-length DOP-3 receptor. Reporter gene assay showed that DOP-3 attenuates forskolin-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 34 publications
(51 reference statements)
2
82
0
Order By: Relevance
“…DOP-4 receptors have been shown to localize in GABA AVL motoneurons, the PQR chemosensory neurons, and other head neurons (Sugiura et al, 2005). Although we do not know whether the C. elegans DA neurons make synapses with neurons expressing DOP-4 receptors, we cannot exclude the possibility that the release of large amounts of extracellular DA after AMPH treatment may lead to spillover of the neurotransmitter to extrasynaptic sites.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…DOP-4 receptors have been shown to localize in GABA AVL motoneurons, the PQR chemosensory neurons, and other head neurons (Sugiura et al, 2005). Although we do not know whether the C. elegans DA neurons make synapses with neurons expressing DOP-4 receptors, we cannot exclude the possibility that the release of large amounts of extracellular DA after AMPH treatment may lead to spillover of the neurotransmitter to extrasynaptic sites.…”
Section: Discussionmentioning
confidence: 72%
“…To date, four DA receptors have been cloned and functionally characterized in C. elegans: the D1-like DA receptors DOP-1 and DOP-4 (Suo et al, 2002;Sugiura et al, 2005); and the D2-like DA receptors DOP-2 and DOP-3 (Suo et al, 2003;Chase et al, 2004;Sugiura et al, 2005). We investigated the involvement of these receptors in AMPH-induced SWIP using knockout lines for each receptor.…”
Section: Amph-induced Swip Requires Dat-1 Expressionmentioning
confidence: 99%
“…The opposite effects of D1 and D2 signaling on adenylyl cyclase activity suggest a simple model to explain the antagonistic effects of coexpressed DA receptor signaling; however, whether or not this antagonism occurs within a single cell remains largely untested. When tested in cell culture experiments, DOP-1 and DOP-3 receptors can increase and decrease cAMP levels, respectively (Sanyal et al 2004;Sugiura et al 2005), but this is not the coupling that we have identified in vivo despite the fact that Gas is expressed in the cholinergic motor neurons and is thus available for coupling to the DOP-1 receptor (Korswagen et al 1997).…”
Section: D1-like Receptors Can Act Through Gaq and D2-like Receptorsmentioning
confidence: 93%
“…The differences in indices between the alleles of the same gene may be caused by side mutation(s) in each of the mutant strains. Although the incomplete suppression of enhancement by dop-3 mutation may suggest the involvement of another dopamine receptor, invertebrate-specific dopamine receptor homolog dop-4(tm1392) (Sugiura et al, 2005) did not appear to be involved as a single mutation or double mutation with dop-3 (K. F. and K. D. K., unpublished observation). Together, these results suggest that D 2 -like dop-3 plays a significant role in the enhancement of 2-nonanone avoidance.…”
Section: Dopamine Signaling Is Required For the Enhancement Of 2-nonamentioning
confidence: 99%